Prediction of Self-Harming Thoughts Based on Early Maladaptive Schemas and Mindfulness - Shohrehalsadat Filsouf; Tayebe Ardi; Elham Mahmodiyan; Sevin Esmaelzadeh; Hanieh Forghani Heris (Health Nexus, 2026)
Self-harming thoughts are among the most important psychological warning signs associated with emotional dysregulation, maladaptive coping, and vulnerability to self-injurious behaviors. The present study aimed to examine the predictive role of mindfulness and early maladaptive schemas in self-harming thoughts among adults referring to psychological clinics in Tehran. This applied study used a descriptive-correlational cross-sectional design. The statistical population consisted of individuals over 18 years of age who referred to private or public psychological clinics in Tehran during the third quarter of 2025 due to anxiety, depression, or other psychological difficulties. Using simple random sampling and based on the Krejcie and Morgan table, 300 participants were selected. Data were collected using the Kentucky Inventory of Mindfulness Skills, Young Schema Questionnaire–Short Form, and Beck Scale for Suicide Ideation. Data were analyzed using Pearson correlation coefficients and simultaneous multiple regression analysis in SPSS version 22. The results showed that total mindfulness was negatively and significantly associated with self-harming thoughts (r = −0.556, p = 0.001), whereas the total maladaptive schema score was positively and significantly associated with self-harming thoughts (r = 0.455, p = 0.002). In the regression analyses, the mindfulness model and schema model significantly predicted self-harming thoughts. Among mindfulness components, only describing without labeling remained a significant predictor (β = 0.244, p = 0.004). Among schema domains, only impaired autonomy and performance significantly predicted self-harming thoughts (β = 0.307, p = 0.002). In the simultaneous model, mindfulness and early maladaptive schemas together explained approximately 40% of the variance in self-harming thoughts (R² = 0.402). These findings suggest that self-harming thoughts are shaped by the combined effects of reduced mindfulness skills and dysfunctional cognitive-emotional schemas. Interventions that strengthen nonjudgmental description of internal experiences and modify autonomy-related maladaptive schemas may help reduce self-harming thoughts.